Traditions of honoring the bear in the Yakut "kurum" celebration - Fedorov, Sviatoslav Igorevich; Semenov, Anatoly Artemovich (Исторический журнал: научные исследования, 2023)
This article presents the results of a study of the bear image in the Yakut hunting culture and the Yakut bear holiday "kurum". The aim is to identify the bear holiday among Yakuts. The cult of bear veneration can be traced in many peoples of Siberia, but until later it was believed that Yakuts had no bear holiday, only in the 19th century R. K. Maak recorded a bear holiday among Yakuts and Tungus population in the Vilyuysk district of Yakutia. The bear festival can also be traced among the Tungus population in the Vilyui district, where they lived closely with the local Yakuts and entered into various ties, which most likely caused the Yakuts to adopt some Tungus traditions. The source base of the work is ethnographic materials of researchers of the XIX-XX centuries, as well as previously unpublished field materials collected in Suntarsky district of the Republic of Sakha (Yakutia). The main conclusion of the study is that the Tungus population of the Vilyui district, who had a fairly well-developed bear cult, took an active part in the formation of the bear ritual "kurum" among the Vilyui Yakuts. In the central and northern regions of Yakutia, the "kurum" festival as a bear ritual is not mentioned, in other words, it was not widespread, although the term itself is found in the Yakut lexicon and means a wedding feast.